Extraction approaches used for the determination of biologically active compounds (cyclitols, polyphenols and saponins) isolated from plant material. Issue 15 (25th April 2018) - Ligor, Magdalena; Ratiu, Ileana‐Andreea; Kiełbasa, Anna; Al‐Suod, Hossam; Buszewski, Bogusław
Abstract: Based on the bioactive properties of certain compounds, such as antioxidant and anti‐inflammatory activities, an interesting subject of research are natural substances present in various parts of plants. The choice of the most appropriate method for separation and quantification of biologically active compounds from plants and natural products is a crucial step of any analytical procedure. The aim of this review article is to present an overview of a comprehensive literature study from the last 10 years (2007–2017), where relevant articles exposed the latest trends and the most appropriate methods applicable for separation and quantification of biologically active compounds from plant material and natural products. Consequently, various extraction methods have been discussed, together with the available procedures for purification and pre‐concentration and dedicated methods used for analysis.